PERANCANGAN PROTOTYPE SISTEM PENGENDALI LAMPU LALU LINTAS PADA MODEL SIMPANG EMPAT - Rahardjo T.S., Kuat; Juana, Endang; Suwatri, Hilman (Jurnal Teknik Elektro, 2009)
This paper describes the prototype design of traffic lights controller for several intersection model which in this paper is implemented for a 4 intersections model. This prototype is using MCS51 Microcontroller Family to control the 4 intersection traffic lights lighting sequence. In this prototype the duration of the lighting sequence are adjustable to cater for different timing need of an intersection. To be able to cater for different intersections there are supporting component needed such as Keypad and LCD for for setting up timing sequence; SEEPROM for storing in setting data and duration for each timer; Decoder as an expander output port for lighting up the traffic lights and 7-segment as the indicator of remainder of duration of time in one direction before change of light. All process is supported by software implemented in Assembly Language.Keywords: microcontroller, timer, traffic lights